EFEKTIVITAS TEAM GAMES TOURNAMENT (TGT) DENGAN QUICK AND SMART TERHADAP AKTIVITAS DAN HASIL BELAJAR MATERI THINGS IN THE CLASSROOM - Gadis Herningtyasari; Ulya Himawati (Universitas Wahid Hasyim Semarang, 2022)
AbstractIn order to realize the ideals of education required appropriate learning. Reality has not been a student-centered learning. The results of interviews of teachers and students gained student learning outcomes is low because students are less enthusiastic and active role in the learning process. The condition can be pursued through Team Games Tournament (TGT) learning model with Quick and Smart which requires students to learn and understand the material. This study aims to determine the effectiveness of TGT aided Quick and Smart about Things in the Classroom material and learningoutcomes in one of state elementary school in Semarang. This study uses pretest-posttest control group design. Sample used are class VA (experimental class) and VB (control group). Sampling using random cluster sampling. The results showed experiment class is more active than control class, more than 80% experimental class students’s activity was high, posttest experimental class’s average was better than control class, N_gain class experimental’s score was high, achieved more than 80% of students posttest experimental group gained value ≥75. These results were confirmed by students and teachers response to learning model applied. Based on this research can be concluded that TGT aided Quick and Smart is effective to increase students’ activity and their learning outcome about Things in the Classroom.Keywords: Activity, Learning Result, Things in the Classroom, TGT Quick and Smart